The Effect of CSR On Brand Loyalty: The Moderating Role of Corporate Reputation and Mediates the Brand Image - Qasim, Saba; Siam, Mohammad R.A; Sarkawi, Mohd Nizam bin M (Asian Journal of Empirical Research, 2017)
Corporate Social Responsibility (CSR) is viewed as a good marketing tool due to its signiﬁcant inﬂuence on customers' practices. The purpose of this study is to investigate the indirect effect of various measurements of CSR on brand loyalty. The study focus on indirect relationship of CSR on brand loyalty mediated with brand image and the study moderates corporate reputation. This is a conceptual paper based on an indirect relationship of CSR on brand loyalty. This article may provide evidence of an indirect relationship between CSR and brand loyalty through the moderating role of corporate reputation and mediated brand images. Our ﬁndings indicate that legal and ethical responsibilities, as two main dimensions of CSR, improve brand loyalty through brand images. Moreover, fulﬁlments of legal and ethical responsibilities play different roles in improving a brand loyalty. This article is an important step in research on the indirect relationship between CSR and brand loyalty and also it mediates brand image as moderated with corporate reputation.